2019
DOI: 10.1210/clinem/dgz248
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Adipose Tissue Expansion, A Missing Link in the Prediction of Birth Weight Centile

Abstract: Context Maternal body mass index (BMI) is associated with increased birth weight but does not explain all the variance in fetal adiposity. Objective To assess the contribution of maternal body fat distribution to offspring birth weight and adiposity. Design Longitudinal study throughout gestation and at delivery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 65 publications
4
16
0
Order By: Relevance
“…Our findings are in agreement with a similar, but smaller, study by Jarvie et al 32 , where abdominal subcutaneous and visceral adipose tissue thickness were measured by ultrasound at mean 12.4 weeks of gestation in 45 pregnant women. The study shows that first trimester visceral adipose tissue thickness, but not abdominal subcutaneous adipose tissue thickness or first trimester BMI, is associated with birthweight centile.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are in agreement with a similar, but smaller, study by Jarvie et al 32 , where abdominal subcutaneous and visceral adipose tissue thickness were measured by ultrasound at mean 12.4 weeks of gestation in 45 pregnant women. The study shows that first trimester visceral adipose tissue thickness, but not abdominal subcutaneous adipose tissue thickness or first trimester BMI, is associated with birthweight centile.…”
Section: Discussionsupporting
confidence: 93%
“…Besides, the authors report an association between first trimester visceral adipose tissue thickness and fetal cord plasma triglyceride at delivery. Of note, fetal cord blood was available from only 23 of the pregnancies 32 . In non-pregnant individuals, fat accumulation in visceral fat tissue and other organs is proposed to occur when the adipocytes in the subcutaneous fat tissue are unable to store triglycerides 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, maternal diet quality (assessed by the Healthy Eating Index-2015) during pregnancy and lactation was positively associated with infant percent body fat (%BF) and fat mass (in kg, by air displacement plethysmography, ADP) at 6 months of age [ 50 ]. Specifically, VAT thickness (measured by ultrasound) in the first trimester explained the variations in the newborn birth weight centile to the greatest extent compared to subcutaneous adipose tissue and BMI [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from a large study including 1173 mother–child pairs (mostly Caucasians) demonstrated that maternal obesity during early pregnancy was associated with a 0.63 standard deviation increase in body mass index (BMI) z-score ( p = 0.006) and a 11.5% increase in sum of skinfold thickness ( p < 0.001) in children at 6 years old (adjusted analysis for maternal covariates) [ 34 ]. More specifically, VAT thickness (measured by ultrasound) in the first trimester explained the variations in newborn birth weight centile to the greatest extent compared to SAT and BMI (R 2 = 15.8%, p = 0.002) [ 35 ]. Interestingly, maternal diet quality (assessed by the Healthy Eating Index—2015) during pregnancy and lactation was positively associated with infant percent body fat (%BF) and FM (in kg, by air-displacement plethysmography (ADP)) at 6 months of age [ 36 ].…”
Section: Adipose Tissue Developmentmentioning
confidence: 99%